Treponema pallidum - Fouch, Sarah (Henry Stewart Talks, 2025)
Clinical presentation and stages of syphilis, Virulence factors, Diagnosis of syphilis non-specific (non-treponemal) test, Specific treponemal tests, Prevention and treatment